Determination of Amino Group Content on Nanosilicas with p-Aminobenzoic Acid Modified Glassy Carbon Electrode Using Copper(II) as Intermedia - Chang, Zhixian; Qu, Jianying; Zhang, Ling; Li, Deliang (Asian Journal of Chemistry, 2011)
In the present work, a p-aminobenzoic acid (p-ABA) modified glassy carbon electrode (GCE) was developed to determine amino group content on g-aminopropyltriethoxysilane modified nanosilica (AMNS) using copper(II) as intermedia by cyclic voltammetry. The method was based on the sensitive response of copper(II) on p-aminobenzoic acid modified glassy carbon electrode and the quantitative reaction of copper(II), 5-nitrosalicylaldehyde and surface amino group content on g-aminopropyltriethoxysilane modified nanosilica. Results were found that the proposed method was of good reproducibility and accuracy and no significant differences from atomic absorption spectroscopy.